2018
DOI: 10.1038/s41598-018-20536-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel global effector mining from the transcriptome of early life stages of the soybean cyst nematode Heterodera glycines

Abstract: Soybean cyst nematode (SCN) Heterodera glycines is an obligate parasite that relies on the secretion of effector proteins to manipulate host cellular processes that favor the formation of a feeding site within host roots to ensure its survival. The sequence complexity and co-evolutionary forces acting upon these effectors remain unknown. Here we generated a de novo transcriptome assembly representing the early life stages of SCN in both a compatible and an incompatible host interaction to facilitate global eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 84 publications
0
35
1
Order By: Relevance
“…To gain further insights into the prevalence of alternative splicing within known effector proteins, the 80 previously identified secreted effector proteins were associated with 371 transcripts. This differs from previous work where 395 transcripts were associated with the 80 effectors in a de-novo transcriptome approach [17]. The main types of alternatively spliced variants for the effector genes included 73 (19.7%) intron retention, 26 (7.0%) alternative 5' donor site, 25 (6.7%) alternative 3' acceptor site, 43 (11.6%) alternative transcription start site, 47 (12.7%) alternative transcription termination site, 4 (1.1%) single exon skipping, and 30 (8.1%) multiple exon skipping.…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…To gain further insights into the prevalence of alternative splicing within known effector proteins, the 80 previously identified secreted effector proteins were associated with 371 transcripts. This differs from previous work where 395 transcripts were associated with the 80 effectors in a de-novo transcriptome approach [17]. The main types of alternatively spliced variants for the effector genes included 73 (19.7%) intron retention, 26 (7.0%) alternative 5' donor site, 25 (6.7%) alternative 3' acceptor site, 43 (11.6%) alternative transcription start site, 47 (12.7%) alternative transcription termination site, 4 (1.1%) single exon skipping, and 30 (8.1%) multiple exon skipping.…”
Section: Resultscontrasting
confidence: 86%
“…The most abundant alternative splicing events were intron retention (30%) and non-mediated decay (15%), with 70% of alternative splicing events changing open reading frame length ( Figure S3 & S4). In comparison, previous work utilizing a de novo transcriptome assembly approach discovered 71,093 genes with 147,910 (2.08 average) transcripts in H. glycines [17] thus demonstrating the importance of using an assembled genome as a part of the transcriptomics pipeline [18].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…A limitation of our study was that just a single biological sample was used in the RNA‐seq. Also, it has been reported that the RNA‐seq was carried out only from a single biological sample in several researches (Geng et al, ; Liu et al, ; Gardner et al, ; Singh et al, ). In the present study, on the basis of RNA‐seq data, secondary and tertiary methods of analyses were used to validate the observed differences.…”
Section: Discussionmentioning
confidence: 99%